A Comparative Study of Problem-Based Learning and Project-Based Learning on Cadets’ Problem-Solving Skills in Vocational Aviation Education - Parjan Parjan; Lady Silk Moonlight; Maulana Anifa Silvia; Faoyan Agus Furyanto; Ahmad Musadek; Anton Budiarto (Fakultas Ilmu Pendidikan Universitas Negeri Surabaya, 2026)
Problem-solving skills are essential competencies for vocational graduates in aviation education, where professional tasks are characterized by high risk, time pressure, and technological complexity. This study examined the effectiveness of Problem-Based Learning (PBL), Project-Based Learning (PJBL), and a combined PBL–PJBL approach in improving the problem-solving skills of cadets at an Aviation Polytechnic in Surabaya. A quantitative method with a quasi-experimental design was employed. A total of 100 first-year cadets were selected through purposive sampling and assigned to four groups: PBL, PJBL, combined PBL–PJBL, and a control group. Data were collected using a validated and reliable questionnaire administered as pretest and posttest, and analyzed using one-way ANOVA, Tukey’s HSD post hoc test, and N-Gain analysis. The results indicate that all experimental learning models significantly improved cadets’ problem-solving skills compared to the control group. The combined PBL–PJBL model demonstrated the strongest overall effect, yielding the highest statistical improvement and a very large effect size. When examined as single-method implementations, PBL produced higher learning gains than PJBL, indicating greater practical efficiency in developing problem-solving skills. These findings suggest that while PBL alone is an effective and efficient instructional approach, integrating PBL and PJBL provides a more comprehensive learning experience that maximizes problem-solving development in aviation vocational education. The study highlights the importance of aligning instructional strategies with the cognitive and operational demands of aviation training contexts.